2018
DOI: 10.1002/ijgo.12721
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐based approach versus culture‐based screening for identification of group B streptococci among women in labor

Abstract: Objective To compare a risk‐based and culture‐based screening approach for identification of group B streptococci (GBS) vaginal colonization using an intrapartum rectovaginal culture as the reference standard. Methods Pregnant women attending the prenatal clinic at Lillebaelt Hospital, Kolding, Denmark, between April 1, 2013, and June 30, 2014, were invited to participate in a prospective observational study. For prepartum culture‐based screening, vaginal and rectal culture samples were obtained and, for refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“… Streptococcus agalactiae or group B streptococcus (GBS) is a leading cause of invasive neonatal infections [1]. The bacterium colonizes the gastrointestinal and genital tracts of humans [2, 3] and up to 44 % of women carry GBS in the vagina during pregnancy [4–8]. Most commonly, GBS infections of newborns occur because of an ascending infection in pregnancy or the newborn becomes colonized during passage through the birth canal [2].…”
Section: Introductionmentioning
confidence: 99%
“… Streptococcus agalactiae or group B streptococcus (GBS) is a leading cause of invasive neonatal infections [1]. The bacterium colonizes the gastrointestinal and genital tracts of humans [2, 3] and up to 44 % of women carry GBS in the vagina during pregnancy [4–8]. Most commonly, GBS infections of newborns occur because of an ascending infection in pregnancy or the newborn becomes colonized during passage through the birth canal [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the screening-based approach, all pregnant women are offered microbiological screening at 35-37 weeks of gestation and culture-positive women are treated. This approach has been found to be more effective at identifying intrapartum GBS colonization than the risk-based approach but necessitates the treatment of more women and is also a more expensive option [14].…”
Section: Introductionmentioning
confidence: 99%
“…Carriage studies [ 6 , 9 ] based on rectovaginal swabs from women with risk factors for EOGBS during delivery, showed a carriage rate of 29 %. This is similar to other Danish as well as international studies [ 19 , 20 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that carriage rates with GBS in pregnant women can vary from 10 to 35 % cultured at gestational week 35-37, although this can only be considered as a qualified guess for the rate at birth since GBS colonization may be transient and vary during pregnancy. [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%